Activation of inositol 1, 4, 5-trisphosphate receptors during preconditioning low-frequency stimulation suppresses subsequent induction of long-term potentiation in hippocampal CA1 neurons. (17th December 2015) - Yamazaki, Y.; Fujii, S.; Goto, J.-I.; Fujiwara, H.; Mikoshiba, K.
Highlights: A train of LFS given prior to the delivery of HFS suppresses LTP induction in hippocampal CA1 neurons. Co-activation of IP3 receptors and NMDA receptors during LFS results in both phosphorylation and dephosphorylation events. Both of these events lead to prolonged activation of group I mGluRs that is responsible for the LTP suppression. These results help us understand how activation of IP3 receptors contributes to the regulation of learning modes. Abstract: We investigated the role of inositol 1, 4, 5-trisphosphate receptors (IP3 Rs) activated during preconditioning low-frequency stimulation (LFS) in the subsequent high-frequency stimulation (HFS)-induced induction of long-term potentiation (LTP) in CA1 neurons in hippocampal slices from mature guinea pigs. Induction of LTP in the field excitatory postsynaptic potential (EPSP) or the population spike (PS) by delivery of HFS (a tetanus of 100 pulses at 100 Hz) to the Schaffer collateral–commissural pathway to CA1 neuron synapses was suppressed when the CA1 synapses were preconditioned by LFS of 1000 pulses at 1 Hz. This effect was inhibited when the preconditioning LFS was applied in the presence of an N -methyl-d -aspartate receptors (NMDARs) antagonist, a metabotropic glutamate receptor (mGluR) antagonist, IP3 R antagonist, a calmodulin-dependent kinase II inhibitor or a calcineurin inhibitor. Furthermore, blockade of group I mGluRs immediately before the delivery of HFS blocked the inhibitory effect of the preconditioning LFS on subsequent induction of LTP by HFS. These results suggest that, in hippocampal CA1 neuron synapses, co-activation of NMDARs and IP3 Rs during a preconditioning LFS results in both phosphorylation and dephosphorylation events that lead to prolonged activation of group I mGluRs that is responsible for the failure of LTP induction.